Specific Polyunsaturated Fatty Acids Can Modulate in vitro Human moDC2s and Subsequent Th2 Cytokine Release - Hoppenbrouwers, Tamara; Fogliano, Vincenzo; Garssen, Johan; Pellegrini, Nicoletta; Willemsen, Linette E. M.; Wichers, Harry J. (Frontiers in Immunology, 2020)
Allergy is becoming a rapidly increasing problem worldwide and in vitro models are frequently used to study the mechanisms behind the different types of allergic response. The dendritic cell (DC)-T-cell model can be used to study sensitization. However, lipopolysaccharide (LPS) is often used to maturate the DCs, but it gives rise to a DC1 phenotype, whereas Th2-driven inflammatory diseases such as allergy are characterized by the involvement of the DC2 phenotype. Our aim was to create a DC2-T-cell human model (human moDC2s) to study in vitro sensitization and validate the model using polyunsaturated fatty acids (PUFAs) that were previously shown to have immunomodulatory properties. We found that the generated DC2s expressed OX40L and drove naive T-cells into IL-13 producing CD4+ effector T-cells. In line with in vivo findings, n-3 long chain (LC) PUFA docosahexaenoic acid (DHA) effectively decreased the DC2s surface expression of OX40L, as well as the IL-12p40 and IL-23 cytokine production by DC2s and subsequently lowered IL-13 production by DC2s-induced effector T-cells. Similar cytokine production effects were found with eicosapentanoic acid (EPA) and arachidonic acid (AA), whilst linoleic acid (LA) increased OX40L surface expression and subsequent T-cell derived IL-13/IFNγ ratios, suggesting an increased risk of allergy development. Altogether, these data show that human moDC2s are able to induce Th2 type IL-13 secretion by T-cells differentiated in the presence of these DC2s, and that this model can be differentially modulated by PUFAs . These results are in line with previous in vivo studies using PUFAs, indicating that this model may be of use to predict in vivo outcomes.